Design & Development of Novel Hybrid Set of Rules for Detection and type of Malignant or Non-Malignant Tumor in Human Brain based on SVM Using Artificial Intelligence Classifier - Anwaar Ahmad Wani, Lone Faisal, Madiha zahoor, Juneed Iqbal (Mathematical Statistician and Engineering Applications, 2022)
Thousands of lives are lost across globe due to the malignant and non-malignant tumor. The detection of brain tumor is very crucial as brain tumor is a life threatening disease and proper treatment and efficient diagnosis is very benefitail. This paper proposes exhaustive computerized crossover set of rules for detection and type of malignant and non-malignant tumor. MATLAB center capacity and photo handling tool stash are used for the proposed method. The proposed framework recognizes and segments a tumor, processes significant boundaries that incorporates tumor length and region. The paper also proposes a contraption that finds elements of mind experiencing tumor and shows the related manifestations and anticipation connection. The proposed framework with the aid of numerous techniques divided for the division for skull recognition and vertical ways for tumor identification, rule based absolutely fluffy sound judgment for mind part influenced realities uncover and morphology for tumor division.Then research also detect the tumor and localization, tumor segmentation and area computation and as an outcome we will be able to recognize the area or location of the tumor